15 OF evaluation for the Cyberknife M6: Comparison between two measurement correction methods for different detectors. (December 2018) - Jurczak, J.; Courrech, F.; Herlevin-Gérard, K.; Buchheit, I.; Marchesi, V.
Abstract : Introduction: For small beams used in stereotactic radiotherapy, extra precautions need to be taken into account when determining dosimetric data used in the modelling of dose calculation algorithms[1] . In this work, we focused on the output factors determination of the Cyberknife M6 (Accuray Inc., Sunnyvale, USA). Measurements were performed with active and passive detectors and with fix collimation. We compared two new sets of corrective factors published by the IAEA (TRS 483) and by Francescon et al., recommended by Accuray[2] and we compared theses corrected results with radiochromic films. Methods: OF were measured with three punctual PTW detectors: 60018 (SRS) and 60008 diodes, 60019 microdiamond and EBT3 Gafchromic films (Ashland Inc., USA) for all the fixed collimators in the reference conditions (SAD = 80 cm, depth = 1.5 cm), 200 MU for each beam. Five measurements were performed for each punctual detector and three for the films. Films were analyzed with the Epson V750 Pro (Epson, Japan) and the ImageJ software (NIH, USA). Results: Application of these two sets of corrective factors enable the reduction of discrepancies (related to small beams measurements challenges) between detectors for collimators greater than or equal to 7.5 mm diameter (see Fig. 1). For the 5 mm fixed collimator, the maximal discrepancy between two detectors is 9.6% without corrections and is reduced to 4.4% and 8% with the Francescon's corrections and with the IAEA respectively. In average, corrected measurements are closer to films measurements with a maximal discrepancy varying from 3.8% to 2% and 2.1% for Francescon and for the IAEA respectively. Conclusions: The two sets of corrective factors give similar OF results with a good agreement between detectors, allowing a better precision for OF modelling in the TPS. Those factors could be extended for the Iris collimator[3] .